Bacterial Proteinaceous Compounds With Multiple Activities Toward Cancers and Microbial Infection - Rodrigues, Gisele; Silva, Gislaine Greice Oliveira; Buccini, Danieli Fernanda; Duque, Harry Morales; Dias, Simoni Campos; Franco, Octávio Luiz (Frontiers in Microbiology, 2019)
In recent decades, cancer and multidrug resistance have become a worldwide problem, resulting in high morbidity and mortality. Some infectious agents like Streptococcus pneumoniae, Stomatococcus mucilaginous, Staphylococcus spp., E. coli. Klebsiella spp., Pseudomonas aeruginosa, Candida spp., Helicobacter pylori, hepatitis B and C, and human papillomaviruses (HPV) have been associated with the development of cancer. Chemotherapy, radiotherapy and antibiotics are the conventional treatment for cancer and infectious disease. This treatment causes damage in healthy cells and tissues, and usually triggers systemic side-effects, as well as drug resistance. Therefore, the search for new treatments is urgent, in order to improve efficacy and also reduce side-effects. Proteins and peptides originating from bacteria can thus be a promising alternative to conventional treatments used nowadays against cancer and infectious disease. These molecules have demonstrated specific activity against cancer cells and bacterial infection; indeed, proteins and peptides can be considered as future antimicrobial and anticancer drugs. In this context, this review will focus on the desirable characteristics of proteins and peptides from bacterial sources that demonstrated activity against microbial infections and cancer, as well as their efficacy in vitro and in vivo.